Politik Identitas Dalam Panggung Pilwana (Studi Kasus Pemilihan Wali Nagari Sungai Jambu Kecamatan Pariangan Kabupaten Tanah Datar) - Metri Hertika; Novi Budiman (Politik Islam, 2022)
This study aims to explaint that identity politics can color the election wali nagari (pilwana) in the guava river in 2021. And this study tries to discuss te main problems of the form of identity politics played by candidate candidates or political elites as a means of gaining power in occupying a position. Therefore, this study shows the identity of ethnic symbols, regions (jorong) through the use of networks of community leaders and supporters who come rom the regin’s own sons in the pilwana.Ormas  Islam  Bermuatan Politik Yang Terlarang  Di Indonesia